Karakteristike magnetronskega ionizacijskega merilnika s hladno katodo v visokovakuumskem (VV) in ultra visokovakuumskem (UVV) področju - Erjavec, Bojan (Materiali in tehnologije, 2001)
A model magnetron gauge was constructed based on the small-size 2 l/s sputter-ion Varian-type pump with additional changes, such as: copper cathode plates, a stainless-steel cathode rod, an electrically insulated housing, a highly electrically insulated high-voltage feed-through and a low stray-field Sm-Co magnet. The last three changes enabled accurate measurements of discharge currents from 0,1 nA to 20 ?$μ$?A. The magnetron cell characteristics were measured against a reference extractor gauge on a UHV gauge comparison system. Nitrogen, hydrogen, argon and helium were selected as the test gases. First, the discharge intensity was measured vs anode voltage in the 10 kV range at different pressures selected in the range from 1x10$^-9$ to 1x10$^-6$ mbar. The discharge intensitz behaviour was similar for all test gases. A maximum discharge intensity which was measured at the higher pressure is hifted towards the higher anode voltage. Then the measuring of discharge current vs nitrogen pressure in UHV and HV at different operating voltages selected in the range from 2,5 to 4,5 kV was followed. An optimum discharge current vs pressure characteristic was measured at an operating voltage of 3,5 kV. It can be approximated, using a power law, with an exponent n = 1,38. A magnetron cell pumping speed in HV was also determined at different operating voltages by measuring the equilibrium nitrogen pressure using a spinning rotor gauge and an equilibrium nitrogen flow rate using the rate of pressure-rise method. At a nitrogen pressure of 1x10$^-6$ mbar and an operating voltage of 3,5 kV, the magnetron-cell sensitivity and pumping speed are 9,3 A/mbar and 0,6 l/s, respectively.
Keywords: magnetronska celica; razelektritev; jakost; potencialna porazdelitev; električna poljska jakost; nelinearnost; nezveznost